An Analysis of Infiltration in Furrow Irrigation Channels With Root Water Uptake - Suma Inna; Muhammad Manaqib; Vika Dwi Samudra; Ruly Erhandi (Journal of Applied Mathematics)
This study discusses infiltration in six irrigation channel types with root water uptake in four types of roots. The mathematical model for the infiltration problem is the Richards equation. This equation is then transformed into a modified Helmholtz equation using the Kirchhoff transformation, dimensionless variables. Subsequently, a numerical solution of the modified Helmholtz equation is obtained using the Dual Reciprocity Boundary Element Method (DRBEM) with a predictor–corrector scheme to result in the numerical values of suction potential, water content, and root water uptake function. In addition, the amount of water absorbed by each root and the water distribution pattern in the channel can be obtained and compared. The results indicate that the minimum water content values occur in both impermeable rectangular and trapezoidal channels, and the highest water uptake values are also observed in the impermeable channels. This is consistent with the physical conditions; as in impermeable channels, water loss downward is limited, and water tends to flow toward the plants.